The Impact of Gina Raimondo's Strategic Policy in the Maritime Economy in the United States and Its Relevance to Indonesia - Snekubun, Elyakim; Suwarno, Panji; Prakoso, Lukman Yudho (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This study examines the impact of Gina Raimondo's strategic policies in the maritime economy in the United States (US) and their relevance to the development of the maritime sector in Indonesia. Raimondo, as US Secretary of Commerce, has introduced policies that strengthen port infrastructure, supply chain digitalization, and maritime technology investment. These policies have succeeded in increasing the competitiveness of the US maritime economy. Their relevance to Indonesia lies in the potential for increasing logistics efficiency, technology integration, and developing maritime policies that support economic growth. By learning from US strategies, Indonesia can strengthen port infrastructure and improve maritime regulations to support sustainable maritime economic growth. The results of this study are expected to provide policy recommendations that can be adapted to the Indonesian context.